Quantitative Defect–Property Correlations in Ti3C2Tx MXenes via Precursor-Controlled Defect Engineering - Hassan, Tufail; Lee, Doyeon; Naqvi, Shabbir Madad; Kim, Myungjae; Oh, Jung‑Min; Park, Sang Woon; Iqbal, Aamir; Cho, Soo Yeong; Hao, Zhiwang; Hussain, Noushad; Khalid, Zubair; Zaman, Shakir; et al. (Nano-Micro Letters, 2026)
Defect engineering holds great promise for tailoring the multifunctional properties of MXenes. However, quantitative correlations between defect and material performance remain largely unexplored due to the lack of a reliable strategy to precisely control defect densities. Here, we demonstrate that the defect density of Ti3C2Tx MXenes—including titanium and carbon vacancies, substitutional oxygen defects, and the associated lattice strain—is precisely controlled by adjusting carbon stoichiometry during TiC precursor synthesis and aluminum content during Ti3AlC2 MAX formation. The defect densities propagate from precursors to final MXenes, enabling the fabrication of a series of Ti3C2Tx MXenes with systematically controlled defect densities. This allows a quantitative correlation between defect density and multifunctional properties including electrical and thermal conductivities, infrared emissivity, electromagnetic shielding effectiveness, Joule heating performance, and oxidation stability. The defect-minimized Ti3C2Tx MXene exhibits outstanding performance, with an electrical conductivity of 26,000 S cm−1, thermal conductivity of 57 W m−1 K−1, electromagnetic shielding effectiveness of 90.5 dB at 10 µm, Joule heating performance of 263 °C at 1.5 V, ultralow infrared emissivity of 0.05, and superior oxidation resistance (activation energy of 72 kJ mol−1). Furthermore, this work establishes a comprehensive quantitative framework linking defect structure to multifunctional performance and stability. Highlights: 1 Titanium vacancies (VTi), carbon vacancies (VC), and substitutional oxygen (SO) defects were precisely tuned in TiC and Ti3AlC2 MAX phases by adjusting C and Al feed ratios, yielding Ti3C2Tx MXenes with systematically varied defect densities. 2 Defect minimization resulted in excellent multifunctional performance, including electrical conductivity of 26,000 S cm−1, thermal conductivity of 57 W m−1 K−1, infrared emissivity of 0.05, EMI shielding of 90.5 dB (at 10 µm), Joule heating of 263 °C (at 1.5 V), and activation energy of 72 kJ mol−1. 3 The defect-minimized MXene exhibited excellent oxidation stability, retaining 90% optical absorption after 4 months in dilute dispersion (0.02 mg mL−1). 4 This study establishes a comprehensive quantitative framework linking precursor-derived defect structures to electrical, thermal, optical, and environmental stability of MXenes.